(Re)imagining elementary social studies : a controversial issues reader - Shear, Sarah B.; Tschida, Christina M.; Bellows, Elizabeth (Educator); Buchanan, Lisa Brown; Saylor, Elizabeth E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"The field of elementary social studies is a specific space that has historically been granted unequal value in the larger arena of social studies education and research. This reader stands out as a collection of approaches aimed specifically at teaching controversial issues in elementary social studies. This book challenges social studies education (i.e., classrooms, teacher education programs, and research) to engage controversial issues--those topics with opposing, often politically, religiously, or are otherwise ideologically charged which make people, especially teachers, uncomfortable--in profound ways at the elementary level. This reader, meant for elementary educators and social studies teacher educators offers an innovative vision from a new generation of social studies teacher educators and researchers fighting against the forces of neoliberalism and the marginalization of our field. The reader is organized into three sections: 1) pushing the boundaries of how the field talks about elementary social studies, 2) elementary social studies teacher education, and 3) elementary social studies teaching and learning. Individual chapters either A) conceptually unpack a specific controversial issue (e.g. Islamophobia, Indian Boarding Schools, LGBT issues in schools) and how that issue should be/are incorporated in an elementary social studies methods courses and classrooms or B) present research on elementary preservice teachers' or how elementary teachers and students engage controversial issues. This reader unpacks specific controversial issues for elementary social studies for readers to gain critical content knowledge, teaching tips, lesson ideas, and recommended resources"-- Provided by publisher.
Keywords: Social sciences -- Study and teaching (Elementary) -- United States.; Education -- Teaching -- Subjects -- Social Science.; Teaching of a specific subject.; Educational: Social sciences, social studies.; elektronické knihy; electronic books